Assessing Creative Thinking in Biology: The Role of Motivation and Open- Ended Tasks - Nurkhairo Hidayati; Iffa Ichwani Putri; Nurul Fauziah; Heny Nurdiana; Andi Andariana (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
Creative thinking is an essential competency in 21st-century education, particularly in biology learning, where many problems require open-ended exploration and multiple perspectives. This study aims to analyze students’ creative thinking in responding to open-ended biology tasks and to examine the relationship between learning motivation and the quality of their creative responses. A mixed-method approach with a descriptive design was employed, involving 252 Grade 11 students from two public senior high schools in Pekanbaru. Data were collected using a 12-item open-ended creative thinking test based on four indicators (fluency, flexibility, risk-taking, and elaboration) and a learning motivation questionnaire based on the ARCS model. Quantitative data were analyzed using descriptive statistics and Pearson correlation, while qualitative analysis was conducted to examine patterns of students’ responses. The results indicate that students demonstrate relatively strong performance in fluency and flexibility, suggesting their ability to generate ideas and consider multiple perspectives. However, their performance in risk-taking is relatively low, indicating limited willingness to propose unconventional ideas. The elaboration of responses also varies among students. Furthermore, the correlation analysis shows no significant relationship between learning motivation and creative thinking (r = 0.034, p = 0.591), suggesting that motivation does not directly predict the quality of creative responses. Therefore, it can be concluded that fostering creative thinking requires not only enhancing students’ motivation but also providing learning environments that support idea exploration, intellectual risk-taking, and deeper reasoning through open-ended tasks.